ANALYSIS OF PROBLEM SOLVING ABILITY BASED ON POLYA'S THEORY OF LAND CADETS IN APPLIED MATHEMATICS COURSE - Nurasiah, Lilis; Barr, Farah Dzil; Irianti, Nathasa Pramudita; Irsal, Nur Aliyyah; Shomad, Zahid Abdush (Universitas Tribhuwana Tunggadewi, 2025)
Purpose: This research aims to determine the initial problem solving ability of land cadets in applied mathematics courses. Methods: This research method is descriptive quantitative, where this method is taken to describe the condition situation with descriptive quantitative description. Abalysis: The research subjects were cadets of the D-IV Land study programme of the National Land College who took applied mathematics courses in the 2024/2025 academic year. The research data studied in this study are cadets' answer sheets on the pre-test. Result and discussion: From the results of the study, it was concluded that the problem solving ability of cadets was in the